2020
DOI: 10.3390/nu12082360
|View full text |Cite
|
Sign up to set email alerts
|

A Low-FODMAP Diet for Irritable Bowel Syndrome: Some Answers to the Doubts from a Long-Term Follow-Up

Abstract: A low-FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides and polyols) diet (LFD) is a possible therapy for irritable bowel syndrome (IBS). This study investigates the short- and long-term efficacy and nutritional adequacy of an LFD and the patients’ long-term acceptability. Patients’ adherence and ability to perceive the “trigger” foods were also evaluated. Seventy-three IBS patients were given an LFD (T0) and after 2 months (T1), 68 started the reintroduction phase. At the end of this period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 50 publications
1
71
1
Order By: Relevance
“…Moreover, the long-term effect of re-challenge on the microbiota is not known. Several studies have raised nutritional concerns about the restrictive phase of the low-FODMAP diet, demonstrating that the reductions in calcium and fibers and long-term effects of this deficiencies are not known [ 212 , 232 , 234 , 235 , 236 ]. In addition, the compliance of patients with the low-FODMAP diet should be further investigated, although the dietitian seems to play a fundamental role [ 237 ].…”
Section: Non-immunologic Adverse Reactions To Foodmentioning
confidence: 99%
“…Moreover, the long-term effect of re-challenge on the microbiota is not known. Several studies have raised nutritional concerns about the restrictive phase of the low-FODMAP diet, demonstrating that the reductions in calcium and fibers and long-term effects of this deficiencies are not known [ 212 , 232 , 234 , 235 , 236 ]. In addition, the compliance of patients with the low-FODMAP diet should be further investigated, although the dietitian seems to play a fundamental role [ 237 ].…”
Section: Non-immunologic Adverse Reactions To Foodmentioning
confidence: 99%
“…Few studies have dealt with this phase of the treatment but a recent report showed that approximately 50% of patients were successful in achieving symptom relief. This study showed the importance of a dietician because many of the initial perceived intolerances were not confirmed during systematic reintroduction [ 95 ].…”
Section: Low Fodmap Dietmentioning
confidence: 99%
“…Low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diet is probably the most popular diet in functional gastrointestinal disorders, where it appears to be effective even in the long-term [ 112 ]. Some authors investigated its role even in the IBD setting.…”
Section: Nutritional Suggestions In Outpatient Managementmentioning
confidence: 99%